PHOTOIONIZATION AND ZEKE PHOTOELECTRON-SPECTROSCOPY OF AR, H2 AND CO2 USING A COHERENT XUV LASER SOURCE - Fielding, H; Softley, T; Merkt, F (1991)
Tunable extreme ultraviolet (XUV) radiation of narrow bandwidth (0.6 cm-1) is generated in the region of 130000 cm-1. This radiation is successfully applied to the study of autoionising Rydberg states of argon and hydrogen, and to record one-photon zero kinetic energy (ZEKE) photoelectron spectra of argon and carbon dioxide. © 1991.